(untitled) (JSSE - Journal of Science & Sustainable Engineering, 2025)
This study aimed to evaluate a technique of Fe ion impregnation on perlite mineral and assess its behavior in a heterogeneous Fenton-like reaction, at room temperature and under acidic and alkaline conditions in the removal of Rhodamine B dye. For the catalyst preparation, a suspension of heptahydrated ferrous sulfate (FeSO4.7H2O) was used, followed by thermal treatment (calcination). Different doses of H2O2 (35% v/v) were applied to evaluate dye removal rates. Fe leaching in reaction media was analyzed. Rhodamine B removal at pH 4, 7, 9, 10, and 11 had the respective removal rates of 99.8%, 57.4%, 73.1%, 77.5%, and 96.9% in 240 minutes of reaction. At pH 12, there was 99.7% removal in 110 minutes of reaction. Reactions performed with low dosages of hydrogen peroxide showed, at pH 4 and 11, removal percentages of 95.8% and 90.2%, respectively, in 150 minutes of reaction. Under the same conditions, at pH 12, the removal percentage was 98.6% in 105 minutes. The synthesized catalyst exhibited satisfactory activity under acidic and alkaline conditions, for three cycles, showing promise for applications in heterogeneous Fenton reactions on a large scale.